Meta-analytic evidence of depression and anxiety in Eastern Europe during the COVID-19 pandemic. Issue 1 (31st December 2022) - Zhang, Stephen X.; Miller, Saylor O.; Xu, Wen; Yin, Allen; Chen, Bryan Z.; Delios, Andrew; Dong, Rebecca Kechen; Chen, Richard Z.; McIntyre, Roger S.; Wan, Xue; Wang, Senhu; Chen, Jiyao
ABSTRACT: Objective: To perform a systematic and meta-analysis on the prevalence rates of mental health symptoms including anxiety and depression during the COVID-19 pandemic in the general population in Eastern Europe, as well as three select sub-populations: students, general healthcare workers, and frontline healthcare workers. Data sources: Studies in PubMed, Embase, Web of Science, PsycINFO, and medRxiv up to 6 February 2021. Eligibility criteria and data analysis: Prevalence rates of mental health symptoms in the general population and key sub-populations during the COVID-19 pandemic in Eastern Europe. Data were pooled using a random-effects meta-analysis to estimate the prevalence rates of anxiety and depression. Results: The meta-analysis identifies and includes 21 studies and 26 independent samples in Eastern Europe. Poland ( n = 4), Serbia ( n = 4), Russia ( n = 3), and Croatia ( n = 3) had the greatest number of studies. To our knowledge, no studies have been conducted in eleven Eastern European countries including Hungary, Slovakia, and Slovenia. The pooled prevalence of anxiety in 18 studies with 22 samples was 30% (95% CI: 24–37%) pooled prevalence of depression in 18 studies with 23 samples was 27% (95% CI: 21–34%). Implications: The cumulative evidence from the meta-analysis reveals high prevalence rates of clinically significant symptoms during the COVID-19 pandemic in Eastern Europe. The findings suggest evidence of a potential mental health crisis in Eastern Europe during the ongoing COVID-19 pandemic. Our synthesis also reveals a relative lack of studies in certain Eastern European countries as well as high heterogeneities among the existing studies, calling for more effort to achieve evidence-based mental healthcare in Eastern Europe. HIGHLIGHTS: The pooled prevalence of anxiety and depression in Eastern Europe were 30% and 27%, respectively. Forty-one per cent of frontline healthcare workers suffered mental health symptoms. Southeastern Europe (Balkans) had lower prevalence of mental health symptoms than the rest of Eastern Europe.